2017
DOI: 10.2196/mhealth.7834
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities of mHealth in Preconception Care: Preferences and Experiences of Patients and Health Care Providers and Other Involved Professionals

Abstract: BackgroundThe importance of the preconception period and preconception care (PCC) are broadly acknowledged and the potential benefits regarding health promotion have been studied extensively. PCC provides the opportunity to identify, prevent, and treat modifiable and nonmodifiable risk factors to optimize the health of couples trying to become pregnant. The prevalence of modifiable and nonmodifiable risk factors in these couples is high, but the uptake of PCC remains low.ObjectiveThe aim of this study is to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 32 publications
(26 reference statements)
0
19
0
Order By: Relevance
“…Each woman will be provided with a free subscription to the mHealth coaching programme ‘Smarter Pregnancy’ (Erasmus MC, University Medical Centre, Rotterdam, the Netherlands) that has been shown to improve nutrition and other lifestyle behaviours in this target population before 45–48. The programme offers personal coaching for 26 weeks, which is based on current personal circumstances, pregnancy, nutrition and lifestyle status.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Each woman will be provided with a free subscription to the mHealth coaching programme ‘Smarter Pregnancy’ (Erasmus MC, University Medical Centre, Rotterdam, the Netherlands) that has been shown to improve nutrition and other lifestyle behaviours in this target population before 45–48. The programme offers personal coaching for 26 weeks, which is based on current personal circumstances, pregnancy, nutrition and lifestyle status.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Besides, they mentioned to find the program to simple and therefore quitted before finishing the 24 weeks of coaching. [39] Conclusions and future perspectives Overall, we can conclude that the ''Smarter Pregnancy'' mHealth coaching program is able to motivate women from more and less deprived neighborhoods to improve their nutrition and lifestyle behaviors. Women who live in more deprived neighborhoods, however, seem to improve their nutrition and lifestyle behaviors more compared to women from less deprived neighborhoods.…”
Section: Comparison With Prior Workmentioning
confidence: 97%
“…89 National studies outside of VA report that only 15 to 33% of women interviewed in the postpartum period had discussed preconception health with their clinicians before their pregnancies. [90][91][92][93] Qualitative data suggest that providers in the VA system rarely ask about or initiate conversations regarding their patients' reproductive goals or plans, 28 which are often important precursors to a discussion of preconception health. Data from a recent national survey of over 2,300 women Veterans indicated that fewer than half (49%) who were currently pregnant or considering pregnancy in the future reported discussions of preconception health risks in the past year.…”
Section: Preconception Care In Vamentioning
confidence: 99%